1986
DOI: 10.3758/bf03203006
|View full text |Cite
|
Sign up to set email alerts
|

Some observations on the Poggendorff and Müller-Lyer tactual illusions

Abstract: Two experiments were conducted in which illusory and nonillusory figures were presented in the right and left tactual fields. Experiment 1 used 24 men (aged 18-24 years) and the Poggendorff'(P)illusion and an alignment (AI) task; Experiment 2 used another 24 men and the MullerLyer (ML) illusion and a line-match (Lm) task. Standard and mirror-image presentations of the figure were used in each case. Nested designs of analysis of variance and analysis of covariance were adopted for comparing left-and right-hand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
23
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Scrutiny of the Lucca et al (1986) paper reveals that the data they present are not really informative regarding the magnitude or the direction of the tactual Poggendorff illusion. First, to obtain their overall mean illusions, they averaged the unsigned setting errors, as did Witkin and Asch (1948) many years ago in their experiments on the rod-and-frame illusion.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…Scrutiny of the Lucca et al (1986) paper reveals that the data they present are not really informative regarding the magnitude or the direction of the tactual Poggendorff illusion. First, to obtain their overall mean illusions, they averaged the unsigned setting errors, as did Witkin and Asch (1948) many years ago in their experiments on the rod-and-frame illusion.…”
mentioning
confidence: 90%
“…Second, Lucca et al (1986) referred to previous work, some of which was their own, which had revealed "inversions," settings in the direction opposite the usual visual effects. Following a procedure adopted by Pasnak and Ahr (1970), Lucca et al (1986) then calculated the mean of all the individual settings that were in the same direction as the visual effect (here called positive effects) and, separately, the mean of all the negative settings.…”
mentioning
confidence: 95%
See 3 more Smart Citations